Innovating Transmission Line Foundations in Mountainous Terrain: A Narrative Literature Review - Mallopa, Nayna; Francisco, Angelene; Galero, Millen Grace; Gallardo, Vanessa (JPAIR Multidisciplinary Research, 2026)
Transmission line projects in mountainous regions encounter persistent engineering challenges due to steep slopes, unstable soils, and logistical constraints. Foundation design, as a critical determinant of reliability and cost efficiency, requires integrated strategies that combine geotechnical rigor, construction management, and resource planning. This study employs a narrative literature review to synthesize research on five interconnected dimensions of foundation performance: terrain characteristics, foundation type selection, geotechnical assessment quality, construction methods, and budget allocation. Results highlight that slope gradient and soil type strongly influence bearing capacity and failure rates; anchor foundations provide time efficiency in accessible sites, while pad and pile foundations remain essential in weak soils. High-quality geotechnical assessments, supported by effective communication between design and field teams, reduce unexpected failures. Mechanized construction methods improve cost efficiency in moderate terrains but lose advantage in rugged zones where mobilization and equipment reliability are compromised. Budget allocation enhances outcomes only when mediated by efficient material logistics. The review concludes that sustainable transmission line foundation design in mountainous terrain requires an integrated approach that links technical rigor, financial planning, and logistics efficiency. This has practical implications for infrastructure planning in the Philippines, where terrain-sensitive strategies can reduce delays and costs. Future research should develop predictive models that combine terrain parameters with supply chain simulations to guide proactive design and investment decisions in the Philippine and Asian context.